Fruit Infestation and Larval Density of Melon Fly, Bactrocera cucurbitae (Coq.) as Influenced by Morphological Traits of Bitter Gourd (Momordica charantia L.) - Laskar, Nripendra; Chatterjee, Hirak (International Journal of Bio-resource and Stress Management, 2023)
Melon fly, Bactrocera cucurbitae (Coq.) (Diptera: Tephritidae) is one of the most important biotic constraints for reaping optimum yield potentiality of cucurbitaceous crops. Due to its peculiar life history and mode of damage it is very much difficult to manage the pest by implementing conventional tactics. Thus, it is important to search for plant characteristics that are associated with survivability and development of the pest. Ten bitter gourd cultivars including open pollinated, hybrids and local accessions were taken to study the effect of morphological traits on fruit infestation and larval density of melon fly. There exist significant variation in percent fruit infestation and larval density per infested fruit in different test cultivars and were correlated positively (r=0.48). Positive correlation of percent fruit infestation and larval density per fruit were derived with fruit weight (r=0.76 and 0.75), length (r=0.71 and 0.72) and diameter (r=0.68 and 0.60). On the contrary, negative correlation were observed with ribs density (r=-0.78 and -0.73), ribs depth (r=-0.24 and -0.18) and skin toughness (r=-0.80 and -0.84) of fruits. Multiple correlations on the impact of morphological traits of fruits on percent fruit infestation and larval density fruit-1 were also derived.